NEUTRON RESPONSE FUNCTION OF BONNER SPHERE SPECTROMETER WITH 6LiI(Eu) DETECTOR - Rasito Tursinah; Bunawas Bunawas; Jungho Kim (Website, 2017)
The detector response function was needed to measure the neutron fluence based on the count rates from Bonner Sphere Spectrometer (BSS). The determination of response function of a BSS with 6LiI(Eu) detector has been performed using Monte Carlo MCNPX code. This calculation was performed for BSS using scintillation detector of 4 mm × 4 mm 6LiI(Eu) which is placed at the center of a set of polyethylene spheres i.e bare, 2